Thermoelectric Properties of Si-Doped In2Se3 Polycrystalline Alloys - Okmin Park; Se Woong Lee; Sang-il Kim (Ceramics, 2022)
Post-metal chalcogenides, including InSe, In2Se3, and In4Se3, have attracted considerable attention as potential thermoelectric materials because of their intrinsically low thermal conductivity, which is attributed to their layered structure with weak van der Waals bonds. In this study, we examined the electrical and thermoelectric properties of Si-doped In2Se3 (In2−xSixSe3, x = 0, 0.005, 0.01, 0.015, and 0.02) polycrystalline samples. Hexagonal α(2H)-In2Se3 phase was synthesized without any impurity, and gradual changes in the lattice parameters were observed with Si doping. Drastic changes were observed for the measured electrical and thermal transport properties at 450–500 K, due to the phase transition from α to β at 473 K. The highest power factors were achieved by the sample with x = 0.015 for both α and β phases, exhibiting the values of 0.137 and 0.0884 mW/mK2 at 450 and 750 K, respectively. The total thermal conductivities of the α phase samples decreased gradually with increasing Si doping content, which is attributed to the point defect phonon scattering by Si doping. The total thermal conductivities of the β phase samples significantly decreased compared to those of the α phase samples. Therefore, the sample with x = 0.015 (In1.985Si0.015Se3) showed the maximum thermoelectric figure of merit values of 0.100 and 0.154 at 450 and 750 K, which are enhanced by 152 and 48% compared with those of the undoped α- and β-In2Se3 samples, respectively.